MERARIQ DALAM PERNIKAHAN SUKU SASAK: ANALISIS KOMUNIKASI DAN DINAMIKA SOSIAL DALAM RITUAL PENCULIKAN - Fairiza, Andre; Widyatama, Rendra (Jurnal Analisa Sosiologi, 2024)
Merariq is a unique customary marriage process among the Sasak people, which is through abduction. This tradition has been passed down through generations to the present day. Literature review indicates that merariq publications are more abundant from cultural, legal, and religious perspectives. Some researchers delve into gender studies and tourism, but the perspective of communication sociology is very rare. This article aims to discuss merariq marriage from the standpoint of communication sociology, explicitly analyzing the patterns of communication relationships among individuals involved in merariq.Researchers employ a qualitative approach with a natural observation method, where primary data excavation is through interviews supplemented by a literature review. Researchers engage five key informants, including customary leaders, cultural observers, individuals who have experienced merariq, and civil marriage registry officials. Researchers conclude that merariq is a kidnapping event in the context of a 'drama' aimed at marrying a woman based on cultural norms. The stages of merariq remain unchanged over time, including pre-merariq, merariq execution, negotiation, inauguration, and post-merariq. Courtship in Merariq employs indirect communication patterns facilitated through mediators. Generally, the communication patterns in each stage of merariq vary, but interpersonal communication patterns occur in many stages. In the inauguration stage, communication patterns arise within a group setting, except for the marriage sermon in a public communication setting. Communication patterns in the negotiation stage are the most dynamic and critical to Merariq's success. In Merariq, society places women in a subordinate position, unequal to men, where women tend to be objectified, and men hold more power over women. This imbalanced gender relationship tends to persist to this day.